2003
DOI: 10.1677/joe.0.1760367
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and time-dependent effects of 17beta-oestradiol on insulin sensitivity in insulin-dependent tissues of rat: implications of IRS-1

Abstract: Numerous studies have suggested that ovarian hormones are able to modulate insulin sensitivity, but their exact role remains unclear. We have investigated whether different doses of 17 -oestradiol mediate changes in insulin sensitivity and if these changes could be related to modifications of insulin receptor substrate-1 (IRS-1). Female rats were ovariectomized and later separated into three groups: untreated; treated with a dose of 17 -oestradiol sufficient to reproduce gestational plasma concentrations of 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 65 publications
(71 reference statements)
3
25
0
Order By: Relevance
“…Indeed, experimental studies confirm that the impact of estradiol on IRS-1 expression in adipocytes is dose and time dependent. 28 Low IRS-1 expression of subcutaneous adipocytes has been recently proposed as a marker of IR, low adiponectin expression/secretion, and accelerated atherogenesis. 27 Because centrally obese women in the present study had similarly high IR, low adiponectin, and signs of accelerated atherogenesis, it is tempting to postulate that the decreased expression of IRS-1 in subcutaneous adipocytes could reflect increased cellular exposure to estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, experimental studies confirm that the impact of estradiol on IRS-1 expression in adipocytes is dose and time dependent. 28 Low IRS-1 expression of subcutaneous adipocytes has been recently proposed as a marker of IR, low adiponectin expression/secretion, and accelerated atherogenesis. 27 Because centrally obese women in the present study had similarly high IR, low adiponectin, and signs of accelerated atherogenesis, it is tempting to postulate that the decreased expression of IRS-1 in subcutaneous adipocytes could reflect increased cellular exposure to estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies (González et al 2000(González et al , 2003Kumagai et al 1993) and clinical observations (Colacurci et al 1998;Karjalainen et al 2001) have demonstrated the importance of estrogen in the maintenance of insulin sensitivity in postmenopausal women. However, the route, dose and type of estrogen used appear to determine the efficacy of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen effects also depend on dose and route of administration (53). Cell-specific delivery of E 2 stimulates beneficial activities without unwanted side effects.…”
mentioning
confidence: 99%